THE FORMATION OF KNOWLEDGE MANAGEMENT SYSTEM IN A COMPANY - O. Malygina (Вестник университета)
During the process of economy’s evolution from the resource-oriented to the one, based on a knowledge, commercial companies will face the problem of re-building its processes, management techniques and methods, even maybe values, directing its activities to the definition, collection, creation, storage, circulation and use of knowledge. The article deals with different models of knowledge management and shows specific instruments of the formation of knowledge management system. It’s based on foreground organizational knowledge resources, maintaining relevance, update and use of knowledge in their activity.